APRESENTAÇÃO - Hélio Tavares de Barros, Fernando; Loff Machado, Lucas; Sipavicius Seide, Márcia (Revista de Letras Norte@mentos, 2022)
Apresentação do Dossiê Temático: Onomástica, da Revista de Letras Norte@mentos.